Canonical and non-canonical Wnt proteins program dendritic cell responses for tolerance - Oderup, Cecilia (2013)
Antigen presenting dendritic cells (DC) interpret environmental signals to orchestrate local and systemic immune responses. They govern the balance between tolerance and inflammation at epithelial surfaces, where the immune system must provide robust pathogen responses while maintaining tolerance to commensal flora and food antigens. The Wnt family of secreted proteins, which control epithelial as well as hematopoietic development and homeostasis, is emerging as an important regulator of inflammation. Here we show that canonical and non-canonical Wnts directly stimulate murine DC production of anti-inflammatory cytokines. Wnt3A triggers canonical β-catenin signaling and preferentially induces DC TGF-β and VEGF production, whereas Wnt5A induces IL-10 through alternative pathways. The Wnts also alter DC responses to microbe- or pathogen-associated molecular patterns (PAMPs), inhibiting pro-inflammatory cytokine induction in response to toll like receptor ligands and promoting DC generation of Foxp3+ regulatory T cells. Moreover, although both Wnts suppress pro-inflammatory responses to bacterial endotoxin and to TLR1/2, TLR7 and TLR9 ligands, Wnt5A but not Wnt3A inhibits IL-6 production in response to the viral mimic, polyinosinic:polycytidylic acid. Wnt family members thus directly and differentially regulate DC functions, an ability that may contribute to the balance between tolerance and inflammation at epithelial sites of exposure to microbes and environmental antigens.